Enhancing Critical Thinking in Middle School Students: Comparing Problem-Based Learning and Search, Solve, Create, and Share Models - Laili, Dewi Nur; Fardhani*, Indra; Mulyati, Yayuk; Fielardh, Khalifatulloh; Habiddin, Habiddin (Jurnal Pendidikan Sains Indonesia, 2024)
Critical thinking skills (CTS) can be enhanced through instructional models. The chosen model should be problem-based and student-centered. The problem based learning (PBL) and search, solve, create, and share (SSCS) models meet these criteria. This study aims to compare the potential of the PBL and SSCS models to enhance students' CTS on the topics of soil and life sustainability. Data collection techniques included interviews, questionnaires, observations, and tests. Data analysis techniques involved descriptive quantitative techniques, percentage analysis, validity and reliability tests, normality tests, homogeneity tests, Wilcoxon tests, and N-gain tests. The validation of the devices received very valid criteria. The N-gain test in the PBL class received moderate criteria, and the SSCS class received high criteria. The results showed that both models could improve students' CTS, but the two classes had different levels of CTS improvement. The treatment using the SSCS model resulted in higher CTS compared to the treatment using the PBL model. The PBL model can enhance higher CTS in the inference aspect, while the SSCS model can enhance higher CTS in the interpretation, explanation, and self-regulation aspects